(untitled) (Research, Society and Development, 2021)
The aim of the study is to understand the work process of nursing technicians who work in the Family Health Strategy teams. The case study has a qualitative approach, based on symbolic interactionism, carried out with eight nursing technicians from the Family Health Strategy of a medium-sized Brazilian municipality. Data were collected through semi-structured interviews and analyzed according to thematic content analysis. The research was approved by the Research Ethics Committee. Participants identify that the Family Health Strategy basically performs curative actions and have daily attributions: pre-consultation, post-consultation and nursing procedures. Relational technologies were identified as the main working tool. As the purpose of the work, they stated that it is to meet spontaneous demand. It appears that the work process of nursing technicians is predominantly focused on curative actions at the individual level, which reinforces the care model centered on the disease. Continuing education is suggested to give new meaning to the work of these professionals. Finally, it emphasizes the need to rethink the training of nursing technicians, so that they develop skills expected to work in primary health care services that meet the health needs of the population, from the perspective of comprehensiveness of health care and for the establishment of work processes that consider the determinants, risks and damages to health.